2016
DOI: 10.1111/1365-2745.12688
|View full text |Cite
|
Sign up to set email alerts
|

Bryophyte traits explain climate‐warming effects on tree seedling establishment

Abstract: Summary Above the alpine tree line, bryophytes cover much of the tundra soil surface in dense, often monospecific carpets. Therefore, when climate warming enables tree seedling establishment above the tree line, interaction with the bryophyte layer is inevitable. Bryophytes are known to modify their environment in various ways. However, little is known about to which extent and by which mechanisms bryophytes affect the response of tree seedlings to climate warming. We aimed to assess and understand the impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 75 publications
3
29
0
Order By: Relevance
“…Therefore, while bryophyte species with different mat thicknesses may differ in their capacity to insulate the underlying soil, such differences do not seem to cause temperature differences at seedling rooting depth, or to be the driver of differences in the performance of these seedlings. Other properties of the bryophytes, such as their effects on nutrient availability (Lett, Nilsson, et al., ), their production of secondary compounds (Lett, Nilsson, et al., ; Soudzilovskaia et al., ) or their impacts on soil microbial community structure (Davey & Currah, ; Davey, Heegaard, Halvorsen, Ohlson, & Kauserud, ; Horton & van der Heijden, ) may thus be more important than insulating capacity for their winter impact on seedling survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, while bryophyte species with different mat thicknesses may differ in their capacity to insulate the underlying soil, such differences do not seem to cause temperature differences at seedling rooting depth, or to be the driver of differences in the performance of these seedlings. Other properties of the bryophytes, such as their effects on nutrient availability (Lett, Nilsson, et al., ), their production of secondary compounds (Lett, Nilsson, et al., ; Soudzilovskaia et al., ) or their impacts on soil microbial community structure (Davey & Currah, ; Davey, Heegaard, Halvorsen, Ohlson, & Kauserud, ; Horton & van der Heijden, ) may thus be more important than insulating capacity for their winter impact on seedling survival.…”
Section: Discussionmentioning
confidence: 99%
“…on 27 August 2013 by cutting the sides and bottom with a serrated knife. Cutting bryophytes from below does not affect their performance as bryophytes have no roots and this approach has been successfully applied before (Lett, Nilsson, et al., ; Stuiver, Wardle, Gundale, & Nilsson, ). All cores were cut at 6 cm depth, as gravel and rocks below this depth underneath P. ciliare usually prevented deeper coring.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this, seedling growth responded less to warming in the presence of shrubs potentially due to competition (Grau et al., ). Further, tree seedlings were more responsive to higher nutrient availability under elevated temperatures at the alpine treeline (Grau et al., ) and under controlled conditions (Hoch, ; Lett, Nilsson, Wardle, & Dorrepaal, ), suggesting that the demand for nutrients at the alpine treeline increases with warming.…”
Section: Relative Importance and Interactions Of Environmental Factorsmentioning
confidence: 99%
“…We found that the moss seedbed had intermediate rates of germination, which could be due to high water retention capacity compared to herbaceous vegetation. In stressful environments, mosses can facilitate recruitment by sheltering seedlings from herbivores and temperature extremes (Wheeler et al 2011;Lett et al 2017).…”
Section: Scarification Experimentsmentioning
confidence: 99%